Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.
Sagot :
Answer:
Step-by-step explanation:
y = 4x + 11, and y = -2x - 1, so
4x + 11 = -2x - 1
6x + 11 = -1
6x = -12
x = -2
y = 4x+11 = 3
y = 4x + 11
y = -2x - 1
4x + 11 = -2x - 1
4x + 2x = -1 - 11
6x = -12
x = -12/6
x = -2
y = 4x + 11
y = 4(-2) + 11
y = -8 + 11
y=3
Answer is (-2,3).
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.